Dilthey´s contribution to hermeneutics and investigative psychology - Rivas Huaman, Rolly Guillermo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Psychology today is an indisputable science, but it was not always so. Philosophers and scientists of the past considered that the study of the subjectivity of man was not science; in this frame appears the figure of the philosopher Wilhelm Dilthey. Since the generalization of the ideas of Auguste Comte, the argument of the defenders of axiomatic, deterministic and positivist truth was that the study of human subjectivity is impossible and unreliable, since it is not verifiable and much less measurable. Dilthey goes beyond Schleiermacher and proposes a Hermeneutics capable of interpreting human behavior.